2010
DOI: 10.5114/aoms.2010.13513
|View full text |Cite
|
Sign up to set email alerts
|

Screening of growth hormone deficiency in short thalassaemic patients and effect of L-carnitine treatment

Abstract: IntroductionEvaluation of growth hormone (GH) in short thalassaemic patients and effect of L-carnitine therapy in those with hormone deficiency.Material and methodsThe study included 30 β-thalassaemic patients aged 13.8 ±1.7 years and 30 children with constitutional short stature as controls. Anthropometric measurements (basal and after 6 months), thyroid profile, insulin-like growth factor-1 (IGF-1) and GH provocation by 2 tests were carried out. Eight patients with inadequate GH response to both clonidine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In the present study, inter and intra‐comparison showed a significant rise in level of IGF‐1. The present study confirms recent studies in humans, pigs, chickens, and rats which revealed that supplementation of carnitine increases plasma IGF‐1 concentrations (Beshlawy et al, 2010 ; Brown et al, 2008 ; Di Marzio et al, 1999 ; Doberenz et al, 2006 ; Heo et al, 2001 ; Keller et al, 2011 ; Keller et al, 2013 ; Kita et al, 2002 ). Instead, the result of the study in patients with liver cirrhosis showed that carnitine supplementation did not affect the IGF1 levels (Ohara et al, 2018 ) also Circulating IGF‐I was not affected by LC treatment on porcine fetal (Waylan et al, 2005 ).…”
Section: Resultssupporting
confidence: 91%
“…In the present study, inter and intra‐comparison showed a significant rise in level of IGF‐1. The present study confirms recent studies in humans, pigs, chickens, and rats which revealed that supplementation of carnitine increases plasma IGF‐1 concentrations (Beshlawy et al, 2010 ; Brown et al, 2008 ; Di Marzio et al, 1999 ; Doberenz et al, 2006 ; Heo et al, 2001 ; Keller et al, 2011 ; Keller et al, 2013 ; Kita et al, 2002 ). Instead, the result of the study in patients with liver cirrhosis showed that carnitine supplementation did not affect the IGF1 levels (Ohara et al, 2018 ) also Circulating IGF‐I was not affected by LC treatment on porcine fetal (Waylan et al, 2005 ).…”
Section: Resultssupporting
confidence: 91%
“…After that, 433 records were excluded, and 213 records entered full-text assessment for eligibility criteria. Finally, 74 studies included in the meta-analysis ( Figure 1 ) [ 6 7 11 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 ].…”
Section: Resultsmentioning
confidence: 99%